2020
DOI: 10.1177/2325967120964884
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Treating Female Soccer Players With ACL Injuries: Hamstring Versus Bone–Patellar Tendon–Bone Autograft

Abstract: Background: Although anterior cruciate ligament (ACL) injuries are common in female soccer players, the optimal graft option for ACL reconstruction is currently unclear. Purpose/Hypothesis: To compare the outcomes of female soccer players after ACL reconstruction using either hamstring tendon autograft or bone–patellar tendon–bone (BTB) autograft. We hypothesized that there would be no difference in clinical outcome scores, return to sport, or retear rates between BTB and hamstring grafts in our study cohort. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 22 publications
0
22
1
1
Order By: Relevance
“…16 However, ACL reconstruction (ACLR) does not always ensure RTS, and about 46% to 67% of females with ACLR return to soccer. 4,5,11,31,32 Younger players and those playing at a high level are more likely to return to soccer. 31 Returning to soccer after ACLR is paired with a high risk of new ACL injury to both knees, especially among young female athletes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…16 However, ACL reconstruction (ACLR) does not always ensure RTS, and about 46% to 67% of females with ACLR return to soccer. 4,5,11,31,32 Younger players and those playing at a high level are more likely to return to soccer. 31 Returning to soccer after ACLR is paired with a high risk of new ACL injury to both knees, especially among young female athletes.…”
mentioning
confidence: 99%
“…31 Returning to soccer after ACLR is paired with a high risk of new ACL injury to both knees, especially among young female athletes. 4,5,13,28,29,39,42 Up to one-third of female soccer players who return to soccer after ACLR sustain a new ACL injury within the first 3.5 years after ACLR. 4,13 The incidence of new ACL injury, especially reruptures, seems to be highest in the first 2 to 3 years after ACLR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Graft failures were 17.6% and 16.8%, respectively, with many failures occurring in the first 6 months, possibly related to graft incorporation or the early resumption of demanding physical activity, and although higher than some studies, are comparable to other authors reporting on younger patients with high demands. [10][11][12] The rate of deep infection was acceptably low, 1.8 %/3% urban/rural. This important and pioneering paper demonstrates that even under challenging conditions, ACL reconstruction can provide clinical stability and good function and quality of life in patients in countries with limited resources.…”
mentioning
confidence: 95%
“…In a study of female soccer players ( n = 90) that had undergone ACL reconstruction, with data available for a minimum of a 2-year follow-up, the outcomes for hamstrings autograft and bone-patellar tendon-bone autografts were very similar ( Britt et al, 2020 ). Notwithstanding, a meta-analysis of 5,561 patients undergoing ACL reconstruction found that hamstrings autografts were less likely than bone-patellar tendon-bone autografts to incur in a contralateral ACL rupture ( Zhou et al, 2020 ).…”
Section: Part 2: Anatomic and Physiologic Variations Of The Hamstrings And Potential Implications For Injury Riskmentioning
confidence: 99%